1999
DOI: 10.1046/j.1440-1681.1999.03170.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Ii in Human Veins: Development of Rapid Desensitization and Effect of Indomethacin

Abstract: SUMMARY 1. The present study investigated whether rapid desensitization (tachyphylaxis) develops after exposure of human hand veins to angiotensin (Ang)II and whether pretreatment with indomethacin affects its development. 2. Venoconstrictor responses to increasing (2–256 ng/min) and constant (50 ng/min) doses of AngII and noradrenaline (NA) infusion were obtained in six healthy male subjects using the dorsal hand vein technique. After pretreatment with indomethacin and placebo, venoconstrictor responses to 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

2001
2001
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 30 publications
1
12
1
Order By: Relevance
“…In the present study, we first demonstrated tachyphylaxis of bronchoconstriction elicited by Ang II in vivo. Although pretreatment with indomethacin significantly inhibited tachyphylaxis of Ang IIinduced vascular constriction in human veins in vitro [13], indomethacin did not affect the tachyphylaxis of Ang II-induced bronchoconstriction in our study. This may be due to differences between in vivo and in vitro studies.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In the present study, we first demonstrated tachyphylaxis of bronchoconstriction elicited by Ang II in vivo. Although pretreatment with indomethacin significantly inhibited tachyphylaxis of Ang IIinduced vascular constriction in human veins in vitro [13], indomethacin did not affect the tachyphylaxis of Ang II-induced bronchoconstriction in our study. This may be due to differences between in vivo and in vitro studies.…”
Section: Discussioncontrasting
confidence: 78%
“…Although rapid desensitization (tachyphylaxis) to Ang II develops in human hand veins in vitro [13], it is unclear whether tachyphylaxis is a factor in bronchoconstriction. We therefore have developed models of Ang IIinduced bronchoconstriction and Ang II-induced bronchial hyperresponsiveness in guinea pigs.…”
mentioning
confidence: 99%
“…All drugs, except for aspirin, were prepared aseptically from fresh opened vials, using 0.9% saline (Baxter, Norfolk, UK). Angiotensin II (Clinalfa, Laufelfingen, Switzerland) was infused intravenously at a dose of 50 pmol min −1 , as previous studies have reported tachyphylaxis with this dose [5]. Noradrenaline (Levophed, Abbott, Maidenhead, UK) was infused at a dose of 50 pmol min −1 [1].…”
Section: Methodsmentioning
confidence: 99%
“…To judge from the present results, the synergistic interaction between AII and either VP or NE may be boosted in hemorrhagic shock through the precipitous releases of large amounts of these hormones. Such important examples of synergism between vasoactive hormones in the maintenance of vascular homeostasis may, in part, explain the conflicting in vivo and in vitro response profiles of AII, as demonstrated by other investigators (23)(24)(25)(26)(27), although this hypothesis could be tested in further experiments.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, AII-receptor signaling domains seem capable of triggering an internalization of AII receptors (23) in what have been described as "coated pits," which then internalize as vesicles that fuse with lysosomes for degradation (26). Recent evidence also suggests that vasodilator prostaglandins, which are released by AII, are involved in AII tachyphylaxis in humans because pretreatment with indomethacin reduces, but dose not abolish, the tachyphylaxis (27).…”
Section: Discussionmentioning
confidence: 99%